2011
DOI: 10.1121/1.3561658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of consonant manner and vowel height on intraoral pressure and articulatory contact at voicing offset and onset for voiceless obstruents

Abstract: In obstruent consonants, a major constriction in the upper vocal tract yields an increase in intraoral pressure (P(io)). Phonation requires that subglottal pressure (P(sub)) exceed P(io) by a threshold value, so as the transglottal pressure reaches the threshold, phonation will cease. This work investigates how P(io) levels at phonation offset and onset vary before and after different German voiceless obstruents (stop, fricative, affricates, clusters), and with following high vs low vowels. Articulatory contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…While both partially phonated stops and fricatives have much more phonation in the first interval than in the other two, stops in all word positions still have more phonation than fricatives in all word positions in the first interval, as shown in Figure 6. This is consistent with an analysis of airflow in stops and fricatives by Koenig et al (2011), who note that '[c]losely-approximated vocal folds entering stops should facilitate phonation and allow it to persist to a higher level of [intraoral pressure], whereas earlier abduction for fricatives would inhibit phonation' (3235). It is also consistent with the comparison of voiceless fricatives and stops in Docherty (1992), who found that when voiceless stops have phonation during the closure, it tends to be longer in duration than the counterpart phonation in fricatives.…”
Section: Phonation Shape: Where 'Edge Vibrations' Are Foundsupporting
confidence: 83%
See 3 more Smart Citations
“…While both partially phonated stops and fricatives have much more phonation in the first interval than in the other two, stops in all word positions still have more phonation than fricatives in all word positions in the first interval, as shown in Figure 6. This is consistent with an analysis of airflow in stops and fricatives by Koenig et al (2011), who note that '[c]losely-approximated vocal folds entering stops should facilitate phonation and allow it to persist to a higher level of [intraoral pressure], whereas earlier abduction for fricatives would inhibit phonation' (3235). It is also consistent with the comparison of voiceless fricatives and stops in Docherty (1992), who found that when voiceless stops have phonation during the closure, it tends to be longer in duration than the counterpart phonation in fricatives.…”
Section: Phonation Shape: Where 'Edge Vibrations' Are Foundsupporting
confidence: 83%
“…'edge vibrations' in Lisker & Abramson 1964) -partial phonation that carries over from the preceding sound or that begins during the transition from a consonant to a vowel -is present during the constriction of stops and fricatives. In a study of intraoral air pressure in German, Koenig, Fuchs & Lucero (2011) find that there is an asymmetry in the amount of intraoral pressure (P io ) observed at obstruent edges: P io is greater at phonation offset (at the beginning of the target consonant) than at phonation onset (after the target consonant), which contributes to differences in the proportion of phonation present at the edges of the closure.…”
Section: Presence Of Phonation In Obstruentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In incomplete neutralisation, the reduction of contrast is not due purely to the physical mechanics of articulation. As pointed out by an anonymous reviewer, the VOT contrast is decreased before low vowels as compared to high vowels; the link between VOT and vowel height is likely mechanical (Chang et al 1999, Koenig et al 2011), rather than an effect of a speaker's grammar per se . Such cases are not normally considered to be incomplete neutralisation.…”
mentioning
confidence: 99%